A level set-based topology optimization approach for thermally radiating structures - Cohen, Brian S.; March, Andrew I.; Willcox, Karen E.; Miller, David W. (Structural and multidisciplinary optimization, 2022)
The need for efficient thermally radiating structures is apparent in many aerospace system designs including satellites, launch vehicles, and hypersonic aircraft. This paper presents a novel level set-based topology optimization approach for designing thermally efficient radiating structures. In this paper, we derive a shape sensitivity of the thermal heat power radiated objective function using the adjoint method. This sensitivity is a necessary ingredient for our gradient-based algorithm. We apply an augmented Lagrangian method to solve an example 2D problem where the goal is to maximize heat power rejected subject to a material volume constraint. The radiating surface is kept fixed during the optimization to maintain a design-independent boundary condition, while the conducting region is optimized. Several solutions are illustrated with varying initial conditions. We also present a case study indicating that maximizing the thermal compliance functional is not sufficient for solving this class of problems.